Diffuse Idiopathic Skeletal Hyperostosis Causing Progressive Dysphagia: A Case Report and Review - Farzin Davoodi; Narges Bazgir; Reza Naseri (Case Reports in Radiology)
Background. Diffuse idiopathic skeletal hyperostosis (DISH) is a rare noninflammatory disorder impacting spinal longitudinal ligament and enthesis. The majority of DISH cases are asymptomatic or have few manifestations. Manifestations include neck pain and stiffness, stridor, breathing disturbances, and dysphagia. Case Presentation. A mid-aged man with progressive dysphagia to solid food was admitted to Loghman Hakim Hospital. In cervical X-ray, a huge ossification in the anterior longitudinal ligament was evident. Eventually, he was diagnosed with DISH. Because of coronary artery disease, conservative treatment was considered for him. Conclusion. DISH is a rare disorder usually asymptomatic. In this case report, we present a DISH case with progressive dysphagia to solid foods.